A study on oxidative stress, hematological and biochemical parameters in copper smelter workers. (3rd July 2017) - Alishahi, Mahin; Malekirad, Ali Akbar; Mandegary, Ali; Abdollahi, Mohammad; Mozaffari, Abbas; Ansari, Mehdi
Abstract: In a cross-sectional study, 44 shift workers at a copper smelter unit who had worked there at least for the last 4 years were selected as subjects and were matched with 44 people as controls. In workers, the mean glutathione peroxidase, catalase and total thiol levels were less than the control group. The average of biochemical parameters was significantly higher in workers. Exposure to high levels of copper and iron, lead, arsenic, and cadmium which are released during the process of copper smelting reduces the amounts of antioxident capacity, which leads to oxidative stress in smelter workers.